ANALISIS ASUHAN KEPERAWATAN DENGAN INTERVENSI INOVASI AROMATERAPI LAVENDER PADA PASIEN CHRONIC HEART FAILURE YANG MENGALAMI KECEMASAN DI RT 08 RW 06, KELURAHAN CENGKARENG BARAT, KECAMATAN CENGKARENG, JAKARTA BARAT - Ririn Alfiah Rianti (2022)
Chronic Heart Failure (CHF) is a condition in which the heart is unable to circulate blood throughout the body, so the supply of oxygen and nutrients is blocked. CHF not only has an impact on physical problems but can also affect the psychology of the sufferer. Psychological problems that occur in CHF patients are anxiety. Anxiety is a normal response to very stressful situations in one's life. Anxiety itself can be overcome one of them by doing aromatherapy therapy. Aromatherapy therapy is an action that uses essential oils to treat discomfort and mental problems such as psychological stress, sadness, and anxiety. One of the aromatherapy used for individuals who experience anxiety is lavender aromatherapy. This analysis aims to determine the results of lavender aromatherapy on anxiety in CHF patients. This analysis uses 2 respondents, namely 1 managed patient and 1 resume patient. At the beginning of the study, the Hamilton Rating Scala for Anxiety (HARS) questionnaire was used. The results of the anxiety assessment in patients under management got a score of 16 interpreted as moderate anxiety and resume patients scored 12 interpreted as mild anxiety. The results of the study after the lavender aromatherapy intervention were re-measured the anxiety scores, namely the anxiety scores decreased in patients under management to 9 interpreted as mild anxiety and patients resumed to 7 interpreted as mild anxiety.